Overcoming Morphosyntactic Challenges in English: A Study of Non-Native University Learners Acquiring Competence as a Foreign Language - Rinaldi, Fahdila Fitri (Universitas Pamulang, 2026)
Foreign learners face significant challenges when learning English morphosyntax because their first language differs structurally from the target language. The different aspects of language create problems which lead to insufficient vocabulary development alongside ineffective communication methods and unsuitable teaching methods. This research aims to identify the fundamental difficulties learners face when learning morphological and syntactic structures of FL while presenting practical educational solutions for enhanced learning. The research incorporates eight international students to perform both qualitative and quantitative analyses. For statistical analysis researchers used t-tests together with Mann-Whitney U tests to examine data obtained from 28 survey participants. In-depth interviews served as the primary data collection method to better understand learner challenges and their learning experiences. According to the study, psychological and social elements together with motivation and anxiety create significant barriers to FL learner achievement. The study points out that specific instructional approaches need to address the problems caused by structural variations between L1 and FL. The research suggests learner-centered methods together with digital media integration and error-based learning and metacognitive strategies to enhance FL morphosyntax comprehension and learning. These strategies are put out as practical ways to get over the obstacles that have been identified and improve the educational process.